The relation between ICT and poverty reduction : the Central Statistical Agency of Ethiopia - Tessema, Ermyas Arega (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Information Science))--University of Stellenbosch, 2010.